New species and new records in Neoibidionini and Hexoplonini (Coleoptera: Cerambycidae: Cerambycinae) - García, Kimberly; Santos-Silva, Antonio (Zootaxa, 2022)
Four new species are described in Neoibidionini (Compsina): Corimbion wappesi, from Guatemala, Zacapa; Neocompsa pilosa, from Paraguay, Itapúa; Neocompsa soniae, from Panama, Chiriquí; and Heterachthes boliviensis, from Bolivia, La Paz. New country record, Trinidad and Tobago, as well as chromatic and morphological variations are reported to Gnomidolon incisum Napp & Martins, 1985 (Hexoplonini), and Compsibidion vandenberghei Heffern, Santos-Silva & Nascimento, 2018 (Neoibidionini, Neoibidionina). Additionally, a key to species of Corimbion Martins, 1970 are provided, and the two new species of Neocompsa Martins, 1965, and the new species of Heterachthes Newman, 1840 are included in a previous key.